An artificial blood vessel fabricated by 3D printing for pharmaceutical application - Esmaeili, Saeid; Shahali, Maryam; Kordjamshidi, Alireza; Torkpoor, Zahra; Namdari, Farshad; Saber-Samandari, Saeed; Khandan, Amirsalar (Mashhad Univ Med Sciences, 2019)
Objective(s): Cardiovascular diseases (CVDs) are the leading cause of mortality in the elderly. A common medical procedure for the treatment of CVDs is the replacement of the blocked or narrowed arteries, which is currently the optimal vascular transplant associated with autograft transplantation. In general, the saphenous veins and radial arteries in the mammary gland are considered to be the selective vessels for vascular substitution. In many cardiac patients, artificial blood vessels (ABVs) are not used for several reasons, including the age of the patient, small size of the veins, previous impressions, and abnormally. Therefore, the consideration of vascular substitute demands is inevitable, especially regarding vascular transplantation with very small diameters and availability of proper alternatives. The present study aimed to develop a novel artificial bio-composite blood vessel using polymer-reinforced and bioceramic nanoparticles. Materials and Methods: The biomechanics and chemical properties of artificial vessels have been investigated to be used in coronary artery bypassing in atherosclerosis as a soft tissue engineering procedure. In this study, thermoplastic polyurethane (TPU) composed of nanocrystalline hydroxyapatite (HA) nanopowder was prepared using the extrusion technique to construct the ABVs. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to investigate the optimum specimen. An important feature of the ABVs was the ability to find the elastic modulus, wettability, and porosity of the veins, which were assessed by fused deposition modeling and 3D printing. Results: The sample containing five wt% of HA had superior mechanical and biological features over the pure sample. Conclusion: According to the results, the narrowed arteries composed of TPU composite with nanocrystalline HA nanopowder had proper chemical stability and mechanical characteristics.
Keywords: Artificial vessel; 3D Printing; Flexible polymer; Bioceramic; Cardiovascular Diseases